Pengaruh Level Penggunaan Sorghum bicolor-Indigofera zollingeriana yang Difermentasi (Sorinfer) terhadap Performa Domba Pejantan: Effect of Fermented Sorghum bicolor-Indigofera zollingeriana (Sorinfer) Inclusion Level on the Growth Performance of Rams (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
This study aimed to evaluate the effect of fermented Sorghum bicolor-Indigofera zollingeriana (Sorinfer) silage at distinct levels on the performance of local rams.  Studies were conducted over 7 weeks using 20 rams, with an initial body weight of 20,90±3,72 kg. Rams were divided into 5 treatments with 4 replicates, consisting of 100% field grass (P0),  75% P0 + 25% Sorinfer (P1), 50% P0 + 50% Sorinfer (P2), 25% P0 + 75% Sorinfer (P3), 100% Sorinfer (P4). Parameters measured were dry matter (DM), ash, crude protein (CP), crude fat (CF), crude fiber (CFi), total digestible nutrient (TDN), and daily weight gain. Data were analyzed using Analysis of Variance (ANOVA), and if a difference was detected, the Duncan Multiple Range Test was used.  Feed treatment had a significant effect (p